'Homing in': South Asian, Muslim young women and their physical activity in and around the home. Issue 3 (2nd September 2018) - Stride, Annette; Flintoff, Anne; Scraton, Shelia
ABSTRACT: Research that focuses on the home as a physical activity setting appears preoccupied with measuring activity. What is less researched is how the home is experienced as a physical activity context. This paper explores the physical activity experiences in and around the home of 13 South Asian, Muslim young women. Data were generated using participatory approaches in focus groups and individual interviews. The research highlights the home and vicinity, as a physical, social and cultural space, significant to these young women's physical activity involvement. However, the home also emerges as an important site in the reproduction of gendered power relations. These young women recount the ways in which expectations on them to undertake traditional gender roles within the home can leave them with less time and energy to be physically active. Despite this, the young women suggest that positions other than 'wife' and 'mother' are envisaged for their future, not least in the ways in which they prioritise their education and schooling. The young women emerge as active agents who navigate diverse expectations and priorities to be physically active on their terms.